Analysis of MicroRNA in Bile Cytologic Samples Is Useful for Detection and Diagnosis of Extrahepatic Cholangiocarcinoma. Issue 1 (14th February 2022) - Uchihata, Yukari; Arihiro, Koji; Kaneko, Yoshie; Shimizu, Tomomi; Marubashi, Yukari; Aoki, Chie; Murakami, Takuya; Ochi, Mayu; Niihara, Nanaka; Ohtsuka, Kohei; Unehara, Rimu; Araki, Yusuke; et al.
Abstract: Objectives: This study aimed to develop reliable biomarkers that improve the ability of bile cytology to diagnose cholangiocarcinoma vs benign biliary lesions. Methods: Many studies indicate that microRNAs (miRNAs) are potential candidates for the early diagnosis of cancer. We analyzed the expression of five tumor-associated miRNAs (miR-31-5p, miR-122-5p, miR-378d, miR-182-5p, and miR-92a-3p) in cytology samples using quantitative reverse transcription polymerase chain reaction. We collected 52 surgically resected tissue samples, 84 cytologic specimens from smears (53 cases of cancer and 31 cases of noncancer), and 40 residual sediments after smearing for routine cytology at Hiroshima University Hospital. Results: The expression of miR-31-5p, miR-378d, and miR-122-5p was significantly higher in cancer tissues than those in normal tissues, while miR-182-5p expression was lower. The expression of miR-31-5p, miR-378d, miR-182-5p, and miR-92a-3p was significantly higher in detached cell samples from smears of cholangiocarcinoma cases than in those from noncancer cases. Conclusions: These results suggest that the analysis of miRNAs in bile cytologic specimens is a promising auxiliary tool for distinguishing cholangiocarcinoma from benign biliary lesions.